Theme Session H - Impacts of human activities and pressures on seafloor ecosystems: past, present and future ... - ICES (ASC 2022 - Theme session H, 2024)
ICES Annual Science Conference Book of abstracts of theme session H: Impacts of human activities and pressures on seafloor ecosystems: past, present and future Conveners: Bryony Caswell (United Kingdom), Jan Vanaverbeke (Belgium), Julian Burgos (Iceland) CM 41: Microplastics, monitoring and the Dublin Bay prawn CM 56: Transboundary marine spatial planning in YSLME requires for cumulative effects assessment at ecosystem scales CM 57: Microplastic ingestion by marine invertebrates – Does it depend on feeding mode? CM 102: The importance of habitat heterogeneity for the diversity of benthic communities from the Western Mediterranean continental shelf CM 109: Sharing benthos: the interplay of human and ecological activities as compounding benthic pressures in light of rebuilding fish stocks in the NW Atlantic CM 134: A unique approach to assessing the impact of low-frequency noise and magnetic fields generated by offshore wind farms on swimming, orientation and dispersal of fish larvae CM 139: Bioregionalisation ...